Analysis of Salt Consumption Patterns and Hypertension Risk in Low-Income Families - Nabila Dwi Ananta; Nur Isnaini (Indonesian Journal of Global Health Research, 2026)
Hypertension is a non-communicable disease with a high prevalence, especially in low-income communities. Excessive salt consumption is a significant factor in increasing the risk of hypertension. This study aims to analyze the relationship between salt consumption patterns and the risk of hypertension in low-income families in Metenggeng Village, Bojongsari District. The study design was cross-sectional, involving 66 respondents selected through purposive sampling. Data were collected using questionnaires and blood pressure measurements. Analysis was performed using the Chi-Square test. The results showed that most respondents with high salt consumption were more likely to experience high blood pressure (78.6%) compared to respondents with low salt consumption (42,1%). With a p-value of 0.003 (<0.05), we conclude that excessive salt consumption patterns are significantly associated with increased blood pressure, thus requiring interventions such as nutritional education and salt restriction to prevent hypertension in vulnerable groups.